Controlling Nutritional Status (CONUT) score for predicting all-cause mortality in patients who underwent percutaneous coronary intervention after acute myocardial infarction: a cohort study - Song, Yang; Han, Su; Zhang, Shiru; Yuan, Yalun; Wang, Meizhu; Sun, Zhaoqing (Frontiers in Nutrition, 2025)
BackgroundControlling Nutritional Status (CONUT) score, a novel marker reflecting the malnutrition, has been demonstrated to predict all-cause mortality and major adverse cardiovascular events (MACE) in a wide range of diseases. The research intends to assess the clinical effects of malnutrition on patients who have percutaneous coronary intervention (PCI) after acute myocardial infarction (AMI).MethodsIn this retrospective observational study, we consecutively enrolled 3258 patients diagnosed with AMI from 2010 to 2016. Patients were categorized into three groups based on the CONUT score: normal, mild malnutrition, and moderate and severe malnutrition. The primary outcome was all-cause mortality. We develop cox proportional hazards models to investigate the relationship between the CONUT score and all-cause mortality among patients who underwent PCI after AMI.ResultsAccording to the assessment via the CONUT score, a total of 43.7% patients experienced mild malnutrition, and 4.8% patients experienced moderate and severe malnutrition. During a median follow-up period of 8.6 years, there were 610 patients (18.7%) suffered from all-cause mortality. As malnutrition severity intensified, the occurrence of the primary endpoint saw a steady rise. After adjusting for multiple variables, the group classified with moderate and severe malnutrition exhibited an odds ratio of 1.56 (95% CI 1.13 to 2.15, p = 0.007) for the primary endpoint. Incorporating the CONUT score augments the prognostic accuracy of the GRACE risk score in predicting all-cause mortality (Absolute Integrated Discrimination Improvement = 0.008, p < 0.001; Category-free Net Reclassification Improvement = 0.144, p = 0.001).ConclusionMalnutrition is prevalent among patients with AMI and is significantly associated with an increased incidence of all-cause mortality. As a nutritional assessment tool, the CONUT score effectively aids in risk stratification and predicts poor prognosis in patients. Additional prospective clinical trials are required to evaluate the influence of nutritional interventions on outcomes in patients undergoing PCI after AMI.